Effect of electrospinning processing variables on polyacrylonitrile nanoyarns. Issue 25 (10th March 2018) - Levitt, Ariana S.; Vallett, Richard; Dion, Genevieve; Schauer, Caroline L.
ABSTRACT: With recent developments in the field of smart textiles, researchers have been working toward fabricating architectures of nanofibers, known as nanoyarns, which mimic the geometry of a conventional yarn. In doing so, one can leverage the unique properties of nanoscale fibers, including high surface‐to‐volume ratio and tunable porosity, for the development of smart garments. In the last 5 years, researchers have produced nanoyarns from a limited number of polymers, including polyacrylonitrile (PAN) and poly(vinylidene fluoride) and its co‐polymers. However, to our knowledge, there has been little research on the solution properties and electrospinning parameters needed to fabricate these higher‐order architectures from nonwoven mats. In this work, a modified electrospinning setup, enclosed in a humidity‐controlled chamber, was developed to fabricate nanoyarns for integration into knitted textiles. We fabricated nanofibers and nanoyarns from PAN/DMF solutions and conducted a systematic study to analyze the effect of solution conductivity, viscosity, and electrospinning parameters (applied voltage, collector distance, and humidity) on fiber and yarn fabrication and morphology. Polymer concentration had a significant effect on fibrous cone and yarn fabrication. Low polymer concentrations resulted in poor cone formation, whereas high concentration resulted in dense cones that were difficult to draw into nanoyarns. Overall, the matrix of electrospinning parameters that resulted in the formation of homogenous nanofiber mats was larger than that of nanoyarn formation. Nanoyarn formation required higher polymer concentration and/or applied voltage than nonwoven mat formation. The influence of these parameters on nanoyarn formation and fiber diameter can be used to expand the library of spinnable nanoyarns and optimize their properties for specific applications. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46404. Abstract :